Investigation of Microsporidia in Patients with Acute and Chronic Urticaria - Karaman, Ulku; Sener, Serpil; Calik, Sinan; Sasmaz, Sezai (Ankara Microbiology Soc, 2011)
Microsporidia species are one of the major causes of severe diarrhea especially in immunocompromised patients, however they also cause infections in immunocompetent subjects. Urticaria, which is a common dermatologic disease may be triggered by drugs, infections, foods or food additives, psychogenic factors and autoimmune, metabolic and malignant diseases. While the etiologic grounds of acute urticaria are generally identified, the etiology remains unknown in most of the chronic urticaria cases. The studies on the roles of parasitic infections in the etiology of urticaria have indicated that the most responsible protozoa are Giardia intestinalis and Blastocystis hominis. However, no data have been found in the literature concerning the relationship between Microsporidia and urticaria. The aim of this study was to investigate the presence of Microsporidia spores in the stool samples of patients diagnosed as acute or chronic urticaria in dermatology clinics and to determine the rates of positivity. All of the samples stained with modified trichrome and calcofluor staining methods were examined microscopically. The samples were accepted as positive when the spores of Microsporidia were detected by both of the staining methods. Microsporidia were detected in 26 (19.7%) of the patients and in 1 (2.8%) of the control subjects. Thus the total rate of positivity was 16% (27/168). In cases with acute/chronic urticaria, microsporidia positivity rate was found significantly higher than the control group (p= 0.028; p< 0.05). No statistically significant difference was detected between Microsporidia positivity and age or gender (p= 0.27 and p= 0.99, respectively; p> 0.05). In conclusion, Microsporidia should be taken into consideration in patients with unknown origin of urticaria. However, advanced studies are needed for supporting the relation between Microsporidia and acute/chronic urticaria.
Akut ve kronik ürtikerli hastalarda microsporidia pozitiflik orani
Keywords: Microsporidia; urticaria; etiology; diagnosis